Dentatorubral Pallidoluysian Atrophy (DRPLA)-A Rare Neurological Disorder (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Dentatorubral pallidoluysian atrophy (DRPLA) is a rare  type of an autosomal dominant progressive late onset  cerebellar ataxia. It is caused by a defect in a gene [CAG  repeat in atrophin-1 (ATN1) on chromosome 12] and results  in damage to the cerebellum, and to its connections within  the central nervous system. It is also known as Haw River  Syndrome and Naito-Oyanagi disease. This disorder seems  to be very rare except in Japan. Patients with DRPLA can  exhibit a variety of psychiatric symptoms in addition to  extrapyramidal and cerebellar symptoms. We report a case  who was 28 years old unmarried man presented at BSMMU,  Dhaka in 2010. The present work highlights the variable  mode of presentation of DRPLA and the difficulty of an  early diagnosis without facility of genetic analysis. The aim  of our report was to describe typical clinical presentations  of the disease without positive family history. Our patient  presented with unsteadiness during walking, irrelevant  behavior and talking, incontinence of urine and stool with  occasional myoclonic seizure and dementia.   DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11367   J Bangladesh Coll Phys Surg 2012; 30: 48-52